THE EFFECT OF INTERACTION VIA SOCIAL MEDIA AND PAST ONLINE SHOPPING EXPERIENCE ON REPURCHASE INTENTION THROUGH TRUST IN TOKOPEDIA APPLICATION USERS IN SURABAYA - Seber, Vincent (Research In Management and Accounting (RIMA), 2018)
This study aims to analyze the effect of interaction via social media and past online shopping experience on repurchase intention through trust in Tokopedia application users in Surabaya. Today, online purchasing through e-commerce is in vogue. Before making a purchase, most people will seek information first to increase their trust, and they can do this by interacting with others. Increasingly sophisticated technology makes this interaction easy because there is already social media. The information shared by someone certainly comes from their experience. E-commerce consumer interaction through social media and consumer shopping experience are important points so that consumers can increasingly trust an e-commerce and repurchase it in e-commerce. The sampling technique used is non probability sampling by means of purposive sampling. The sample used in this was 150 respondents. The requirements of respondents in this study were at least 17 years old who had made purchases at Tokopedia at least once in the last two months in Surabaya. Data was collected using a questionnaire. The data analysis technique used is SEM analysis with the LISREL program. The results of the study prove that interaction via social media and the past online shopping experience have a significant effect on trust. Trusts have a significant effect on repurchase intention. Interaction via social media and past online shopping experience has a significant effect on repurchase intention through trust.